10 MeV proton irradiation effects on GaInP/GaAs/Ge concentrator solar cells and their component subcells - Ochoa, M.; Yaccuzzi, Exequiel Eliseo; Espinet-González, P.; Barrera, Marcela Patricia; Barrigón, E.; Ibarra, María Luján; Contreras, Y.; Garcia, Javier Andrés; López, E.; Algora, C.; Alurralde, Martín Alejo; Godfrin, E.M.; et al. (Elsevier Science, 2017)
Fil: Yaccuzzi, Exequiel. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina